2021
DOI: 10.1088/1361-6463/ac2385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pore spacing in barrier coatings on the mass transport through plastics—a simulative and experimental approach

Abstract: In many applications, the use of plastics is only made possible by functionalizing them with coatings for barrier against gases or flavors. These coatings are often produced in low-pressure processes such as plasma enhanced chemical vapor deposition or physical vapor deposition processes. Mass transport through these systems takes place mainly through pores in the nanoand micrometer range. A lot of research has been done to describe the mechanisms of permeation through these thin films under consideration of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…They used the ILT to estimate D and S coefficients of each layer. Recognizing the defective properties of the AlO x barrier coating, they estimated an effective D. For this, they applied an area fraction model that assumes the defects to be filled with polymer and factors in the influence of defect spacing as described elsewhere [20,22,25]. Using WVTR measurements of single-barrier systems to calculate multi-barrier systems with their model, they found that defects were the dominant diffusion pathway.…”
Section: Expanding the Scope Of Defect Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…They used the ILT to estimate D and S coefficients of each layer. Recognizing the defective properties of the AlO x barrier coating, they estimated an effective D. For this, they applied an area fraction model that assumes the defects to be filled with polymer and factors in the influence of defect spacing as described elsewhere [20,22,25]. Using WVTR measurements of single-barrier systems to calculate multi-barrier systems with their model, they found that defects were the dominant diffusion pathway.…”
Section: Expanding the Scope Of Defect Modellingmentioning
confidence: 99%
“…They found that the relation of defect area and resulting flow rate is not linear, which could be partially explained by the significant flow reduction due to defect cluster formation. In a following paper, Wilski et al [25] validated the simulation model with an experimental approach, emulating a porosity with defined pore sizes and distances by precise laser drilling of a stainless-steel foil that subsequently was bonded with a PET film. The measurements showed good agreement with the simulation data, confirming the mitigating influence on mass flow of adjacent pores.…”
Section: Expanding the Scope Of Defect Modellingmentioning
confidence: 99%
See 3 more Smart Citations